1997
DOI: 10.1021/jf9700788
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mass Distributions of Heat-Induced β-Lactoglobulin Aggregates

Abstract: The aggregates in heated bovine β-lactoglobulin solutions were separated by high-performance size-exclusion chromatography, and molecular characteristics were measured on-line using multiangle laser-light scattering detection (SEC-MALLS). This technique was proven to be a very useful and valuable approach for characterization of heat-induced β-lactoglobulin aggregates. Using TSK G2000 SWXL and TSK G4000 SWXL silica gel columns connected in series, aggregates up to a molecular mass of 4 × 106 Da could be separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
80
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 21 publications
15
80
0
Order By: Relevance
“…It must be noted, however, that a possible urea-induced dissociation of high molecular weight aggregates into smaller ones cannot be excluded. It is possible, as previously suggested by Hoffman et al [14], that some disulphide linked aggregates had formed larger ones via noncovalent interactions. On the other hand, our results suggest that even if noncovalently linked aggregates were formed at a high proportion, they were rapidly converted into disulphide bonded aggregates.…”
Section: Nature Of Stabilising Forces Involved In Formed Aggregatessupporting
confidence: 54%
See 1 more Smart Citation
“…It must be noted, however, that a possible urea-induced dissociation of high molecular weight aggregates into smaller ones cannot be excluded. It is possible, as previously suggested by Hoffman et al [14], that some disulphide linked aggregates had formed larger ones via noncovalent interactions. On the other hand, our results suggest that even if noncovalently linked aggregates were formed at a high proportion, they were rapidly converted into disulphide bonded aggregates.…”
Section: Nature Of Stabilising Forces Involved In Formed Aggregatessupporting
confidence: 54%
“…Hoffmann et al [14] showed that noncovalent interactions are of minor importance in the formation of b-Lg aggregates after heating at neutral pH and 65°C. They postulated the prominent role of disulphide bonds.…”
Section: Nature Of Stabilising Forces Involved In Formed Aggregatesmentioning
confidence: 99%
“…4,9,10 The heat-induced denaturation and aggregation are also affected by pH and ionic environment of the medium. 11,12 For valueadded industrial applications of WP, the composition and the changes in both the physico-chemical and functional properties need to be accurately analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Each monomer has a molecular weight of 18.3 kDa, contains 162 amino acid residues, two disulphide bonds (C106-C119 and C66-C160) and one free cysteine residue (C121) [6][7][8] . Upon heating, betalactoglobulin dissociates into monomers, leading to exposure of hydrophobic groups and the free sulfhydryl group [9,10] . This then gives rise to aggregation and/or polymerization [4,5,9,11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Upon heating, betalactoglobulin dissociates into monomers, leading to exposure of hydrophobic groups and the free sulfhydryl group [9,10] . This then gives rise to aggregation and/or polymerization [4,5,9,11,12] . Beta-lactoglobulin is sensitive to heating at 60-100°C.…”
Section: Introductionmentioning
confidence: 99%